Local blockage effect for wind turbines. (June 2015) - Nishino, Takafumi; Draper, Scott
Abstract: This paper presents a combined theoretical and CFD study on the fluid-mechanical limit of power extraction by a closely-spaced lateral array of wind turbines. The idea of this study originates in recent studies on the array optimisation of tidal/marine turbines, for which the power coefficient of each turbine is known to increase significantly if the lateral spacing between turbines, or the local blockage, is optimised. The present study, using 3D Reynolds- averaged Navier-Stokes (RANS) simulations of a boundary-layer flow over a closely-spaced lateral array of up to 9 actuator discs, suggests that a similar—albeit less significant—power increase due to the effect of local blockage can be achieved even for wind turbines. A possible theoretical approach to estimating this power increase is also discussed.